Kebersihan Lingkungan dan Krisis Air Bersih di Desa Jandi Meriah: Perspektif Masyarakat Lokal - Silvia Tabah Hati,; Dila Alvina,; Damai Yanti Tambunan,; Ika Fitria Ningsih,; Ismanora Lubis,; Eka Pratiwi, (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
This study aims to explore the relationship between environmental cleanliness and the water scarcity crisis in Jandi Meriah Village, as well as evaluate the roles of the government and non-governmental organizations (NGOs) in addressing these issues. Utilizing a qualitative approach, the research combines in-depth interviews and focus group discussions to gain comprehensive insights into the community's views on environmental cleanliness and the availability of clean water. The research method involves conducting interviews with 10-15 purposively selected respondents, including the village head, farmers, and housewives. These interviews are guided by semi-structured questions to identify key patterns and themes related to environmental cleanliness and water scarcity. Additionally, focus group discussions will be held with 2-3 groups, each consisting of 8-12 participants, to gather collective perspectives on the challenges and potential solutions. The findings reveal a significant interconnection between environmental cleanliness and the water scarcity crisis in Jandi Meriah Village. Ineffective waste management and poor sanitation contribute to water source contamination, while the lack of access to clean water exacerbates environmental cleanliness and public health issues. Major identified challenges include inadequate infrastructure, limited resources, and low community awareness. The roles of the government and NGOs in providing infrastructure and education are crucial but face challenges in coordination and implementation. The study concludes that there is a need for improved waste management infrastructure and clean water distribution, as well as enhanced community education on hygiene and water management. Better collaboration between the government and NGOs is essential for effectively addressing these issues. Regular evaluation and monitoring are also recommended to ensure the success of the implemented solutions.